Belgisch Congo (1927-1930) in de herinneringen van de Poolse dokter Henryk Gordziałkowski - Czarnecka, Bożena (Department of Dutch and South African Studies, Faculty of English, 2008)
The memoirs of Gordziałkowski, inspired by a three-year stay in the Belgian Congo and published in 1934 under the title Czarny sen (The Black Dream), constitute a wellconstructed text written in a lively, vibrant language, combining elements of reality and adventure in an interesting way. In this non-voluminous book, Gordziałkowski describes colonial reality from the perspective of an ‘Other among Others’. This picture is in many respects related to Flemish colonial literature’s more or less stereotypical image of the colonies, yet it simultaneously depicts certain issues in a significantly different way. In 1959 the book was republished, which could not be a mere coincidence taking into account the development of the political situation in Africa and in Poland itself. For various reasons, the publisher edited and manipulated the text to the extent that the 1959 version effectively inverts the meaning of the original. Such adjustment of a text to new circumstances casts new light on the relationship between literature and external reality.
Keywords: the Belgian Congo; travel writing; image of the Belgian Congo in Flemish and Polish literature